ANALISIS PENERAPAN PENGENDALIAN INTERN PADA SUMBER DAYA MANUSIA DALAM PENINGKATAN KINERJA PERUSAHAAN PADA KANTOR CABANG PT MEDIKON PRIMA LABORATORIES - Alfian, Ryan Allif; Harmain, Hendra (Jurnal Bina Bangsa Ekonomika, 2025)
Medikon management understands the importance of human resources in building and implementing a strong quality assurance system and producing high-quality products. This study aims to analyze the application of internal control on human resources (HR) in an effort to improve company performance in PT Medikon Prima Laboratories branch offices. This study uses a qualitative method with data collection techniques through in-depth interviews, observations, and analysis of related documents. The results of the study show that the effectiveness of internal control can be improved through better human resource management. Some of the key recommendations include continuous training to improve employee competence and compliance, revision and development of SOPs relevant to current operational needs, and optimization of the use of the Salesmart application to support work efficiency and data integration.